2023
DOI: 10.1001/jamanetworkopen.2022.53285
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Temozolomide Chemotherapy With or Without Interferon Alfa Among Patients With Newly Diagnosed High-grade Gliomas

Abstract: ImportanceHigh-grade gliomas (HGGs) constitute the most common and aggressive primary brain tumor, with 5-year survival rates of 30.9% for grade 3 gliomas and 6.6% for grade 4 gliomas. The add-on efficacy of interferon alfa is unclear for the treatment of HGG.ObjectivesTo compare the therapeutic efficacy and toxic effects of the combination of temozolomide and interferon alfa and temozolomide alone in patients with newly diagnosed HGG.Design, Setting, and ParticipantsThis multicenter, randomized, phase 3 clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Despite these interventions, tumor recurrence is common, typically within 6.9 months, leading to a median survival time of only 12 to 15 months post-diagnosis [ 315 ]. Moreover, associating temozolomide with alfa interferon increases the overall survival in patients [ 316 ].…”
Section: Comparative Studies: Gliomas Vs Other Tumor Entitiesmentioning
confidence: 99%
“…Despite these interventions, tumor recurrence is common, typically within 6.9 months, leading to a median survival time of only 12 to 15 months post-diagnosis [ 315 ]. Moreover, associating temozolomide with alfa interferon increases the overall survival in patients [ 316 ].…”
Section: Comparative Studies: Gliomas Vs Other Tumor Entitiesmentioning
confidence: 99%
“…The newest clinical trials showed that GD2 and B7‐H3 CAR‐T cells therapies following standard radiotherapy are beneficial and safe for H3 K27M DMGs or DIPGs 230,231 . Additionally, a latest randomized clinical trial demonstrated the patients undergoing concurrent radio‐chemotherapy with interferon α had a longer survival time than those without interferon α in high‐grade gliomas 232 . The oncolytic virus Delta‐24‐RGD is recently reported to elicit an elevated sensitivity of H3 K27M DMGs to radiotherapy by increasing the trafficking of CD4 + and CD8 + cells to the tumor niche, and the downregulation of kinase activities in DDR system 233,234 .…”
Section: Radio‐resistance and Current Radio‐sensitization Strategiesmentioning
confidence: 99%
“…230,231 Additionally, a latest randomized clinical trial demonstrated the patients undergoing concurrent radio-chemotherapy with interferon α had a longer survival time than those without interferon α in high-grade gliomas. 232 The oncolytic virus Delta-24-RGD is recently reported to elicit an elevated sensitivity of H3 K27M…”
Section: Combination With Immunotherapy and Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of recombinant IFN therapy has been demonstrated in a randomized clinical trial involving high-grade glioma patients. The overall survival was improved upon treatment with temozolomide and IFNα, demonstrating the benefits of combination treatment over the conventional use of temozolomide alone ( 108 ). In addition, the combination of IFNα with BCNU and radiation therapy showed increased overall survival among high-grade glioma patients, thus demonstrating the safe and feasible use of IFNs with other cancer therapies ( 109 ).…”
Section: Type I Interferons In Brain Tumor Immunotherapymentioning
confidence: 99%